2020
DOI: 10.37616/2212-5043.1146
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Trimetazidine with Allopurinol in Prevention of Contrast Induced Nephropathy After Coronary Angiography

Abstract: Objectives: Contrast-induced nephropathy is considered a serious complication following coronary angiography increasing morbidity and mortality. Various drugs have been assessed to reduce the incidence of contrast-induced nephropathy. In this study, we compared trimetazidine and allopurinol as a pharmacological measure to reduce the incidence of contrast-induced nephropathy. Methods: One hundred and twenty patients undergoing coronary angiography with baseline creatinine clearance more than 30 ml/minute were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Now, increasing studies have reported that PCI has become the best and preferred treatment option for AMI, saving many lives. With the popularization of PCI technology and more patients undergoing PCI operation, there has been an increase in the cases of contrast-induced nephropathy (CIN), which is one of the major reasons for iatrogenic renal failure, increasing the risk of death during hospitalization, hospitalization expenses, and hospital stays[ 4 - 6 ]. Since there are many side effects of drug therapy in elderly patients with cardiovascular diseases in China, PCI is more often used, thus leading to a higher incidence CIN.…”
Section: Introductionmentioning
confidence: 99%
“…Now, increasing studies have reported that PCI has become the best and preferred treatment option for AMI, saving many lives. With the popularization of PCI technology and more patients undergoing PCI operation, there has been an increase in the cases of contrast-induced nephropathy (CIN), which is one of the major reasons for iatrogenic renal failure, increasing the risk of death during hospitalization, hospitalization expenses, and hospital stays[ 4 - 6 ]. Since there are many side effects of drug therapy in elderly patients with cardiovascular diseases in China, PCI is more often used, thus leading to a higher incidence CIN.…”
Section: Introductionmentioning
confidence: 99%